Multiparametric Magnetic Resonance Imaging in the Diagnosis of Prostate Cancer: A Systematic Review. Issue 9 (September 2016) - Haider, M.A.; Yao, X.; Loblaw, A.; Finelli, A.
Abstract: A systematic review was conducted to investigate the use of multiparametric magnetic resonance imaging (MPMRI) followed by targeted biopsy in the diagnosis of clinically significant prostate cancer (CSPC) and to compare it with transrectal ultrasound-guided (TRUS-guided) systematic biopsy in patients with an elevated risk of prostate cancer who are either biopsy-naive or who have a previous negative TRUS-guided biopsy. MEDLINE, PubMed and EMBASE (1997 to April 2014), the Cochrane Library and six relevant conferences were searched to find eligible studies. Search terms indicative of 'prostate cancer' and 'magnetic resonance imaging' with their alternatives were used. Twelve systematic reviews, 52 full texts and 28 abstracts met the preplanned study selection criteria; data from 15 articles were extracted. In patients with an elevated risk of prostate cancer who were biopsy-naive, MPMRI followed by targeted biopsy could detect 2–13% of CSPC patients whom TRUS-guided systematic biopsy missed; TRUS-guided systematic biopsy could detect 0–7% of CSPC patients whom MPMRI followed by targeted biopsy missed. In patients with an elevated risk of prostate cancer who had a previous negative TRUS-guided biopsy, MPMRI followed by targeted biopsy detected more CSPC patients than repeated TRUS-guided systematic biopsy in all four studies, with a total of 516 patients, but only one study reached a statistically significant difference. In patients with an elevated risk of prostate cancer who are biopsy-naive, there is insufficient evidence for MPMRI followed by targeted biopsy to be considered the standard of care. In patients who had a prior negative TRUS-guided systematic biopsy and show a growing risk of having CSPC, MPMRI followed by targeted biopsy may be helpful to detect more CSPC cases as opposed to a repeat TRUS-guided systematic biopsy. Highlights: A systematic review on MPMRI in diagnosing prostate cancer. MPMRI targeted biopsy is not recommended in elevated-risk biopsy-naïve patients. MPMRI targeted biopsy may be helpful in growing-risk negative-biopsy patients.